Allgrove syndrome in childhood: a case report and review of the literature - Koathal, Moataz B.; Azhar, Muhammad; Shaikh, Mishraz; Shayba, Nabil A.; Malkani, Izzat; Ajlan, Ziyad A. (International Surgery Journal, 2025)
Allgrove syndrome is an autosomal recessive disease which is characterized by Achalasia, Alacrimia and adrenocorticotropic hormone (ACTH) - resistant adrenal deficiency with progressive neurological manifestations. Allgrove syndrome is caused due to mutations in AAAS gene, localized on chromosome 12q13. This report relates to a 5 years old female child who had complaints of vomiting, fever, cough, hyperpigmentation and poor weight gain. Barium swallow, ophthalmic examination and ACTH stimulation test proves that patient has Allgrove’s syndrome. Management consisted of initiation of cortisone therapy which was successful in improving the hyper pigmentation. Patient was planned for surgical intervention for achalasia cardia on follow-up. Allgrove’s syndrome may be an under diagnosed disorder. High index of suspicion is needed when patients present with such complex symptoms. Diagnosing and timely intervention helps in reducing the morbidity and mortality.